A Proving and Case of Encyclia cordigera - Williams, Sally (Homœopathic Links, 2018)
This article presents the proving and a case of the Central American orchid Encyclia cordigera. Features of the proving are discussed along with a case of vertigo and scoliosis, including an analysis using the Plant Theory.
Keywords: Encyclia cordigera; Orchids; Vertigo; Scoliosis; Balance; Harmony; Fibonacci's number; Sacred geometry